Tendencias actuales en el matrimonio en China - Botton Beja, Flora (El Colegio de México, 2017)
Marriage, a key element of Chinese society, has experienced a great transformation since the midtwentieth century. From being a transaction arranged by the parents, it is now viewed as a choice based upon the free will of both partners. This change has been promoted by the state through the marriage laws of 1950, 1980 and 2001, which have contributed towards radical shifts in family and society. Nevertheless, traditional principles still influence marriage in China. This paper studies recent trends in marriage in contemporary China including thoughts about divorce, conjugal rights, new ways of meeting partners and the emerging public discussion on samesex marriage.